Sara Rovira Esteva, Lengua y escritura chinas. Mitos y realidades, Barcelona, Bellaterra, 2010, 480 pp. - Martínez-Robles, David (El Colegio de México, 2013)
Sara Rovira Esteva, Lengua y escritura chinas. Mitos y realidades, Barcelona, Bellaterra, 2010, 480 pp.